Influence of student factors on entrepreneurial intentions: Evidence from Nigeria - Adeoye, Olumuyiwa Oluseun; Olubiyi, Timilehin Olasoji (Faculty of Business & Economics, Universitas Islam Indonesia, 2024)
Purpose – This study aims to identify the factors influencing entrepreneurial intentions among private university students in South-West Nigeria, and to determine their significance.Methodology – The study population consisted of final-year students from the Faculty/College of Business and Social Sciences across 11 selected private universities in South-West, Nigeria, offering entrepreneurship courses. This study used a sample of 623 students. Data were collected using a self-developed instrument with a reliability coefficient of 0.847 for student-related factors and 0.80 a entrepreneurial intentions. The Relative Significance Index (RSI) and multiple regression analyses were used.Findings – The results revealed that most students perceived several factors as influential on entrepreneurial intention. The key factors were students’ personal factors, family history, technical abilities, and parental attitude. Despite recognizing these influences, many students lacked the skills to solve challenges and effectively utilized technical literature and other information sources. Multiple regression analysis indicated that student parental attitude, student personal factors, and technical abilities significantly influenced entrepreneurial intentions.Implications – This study highlights the importance of enhancing students' personal factors, technical abilities, and parental attitudes to foster entrepreneurial intention. Educational institutions and policymakers should focus on these areas to cultivate an entrepreneurial mindset among students.Originality – This study provides empirical evidence on the determinants of entrepreneurial intentions among private university students in Nigeria, contributing to a broader understanding of how personal, familial, and technical factors shape entrepreneurial aspirations.